Brief History of Group Psychotherapy Congresses at Bergama Asclepion - Osman İsmail Özdel; Hayriye Dilek Akdogan; Ilgaz Akdoğan (Lokman Hekim Dergisi)
In Asklepions, which were ancient hospitals, treatment methods that were considered quite advanced for their time were applied. Asklepion of Pergamon is one of the places where the first psychiatric approach to patients and group psychotherapy practices were performed in the history of medicine. Based on this historical background, Bergama Asklepion International Group Psychotherapy Congresses have been held in Asklepion of Pergamon (today Bergama in Türkiye) since 1984. The 48th of these congresses will be held in 2025. This monograph was written to explain the brief history and current function of the Bergama Asklepion International Group Psychotherapy Congresses.